1973
DOI: 10.1002/neu.480040608
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion of glycine and serine in a synaptosome fraction isolated from the spinal cord, medulla oblongata, telencephalon, and cerebellum of the rat

Abstract: SUMMARYThe metabolism of glycine was studied in vitro using preparations of synaptosomes (P2) isolated from the spinal cord, medulla oblongata, telencephalon, and cerebellum of the rat. The content of aspartate, glutamate, glutamine, serine, threonine, glycine, and alanine was determined in the crude synaptosomal fraction (P2) from the four regions of the CNS. I n general, the content of the amino acids in the subcellular fraction from the medulla oblongata and spinal cord resembled one another whereas the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…It is interesting that except for glutamate, the levels of glycine in the synaptosomal preparations from spinal cord and medulla are the highest of all the amino acid measured (Osborne et al, 1973;McBride et al, 1973).…”
Section: B !!! Vitro Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…It is interesting that except for glutamate, the levels of glycine in the synaptosomal preparations from spinal cord and medulla are the highest of all the amino acid measured (Osborne et al, 1973;McBride et al, 1973).…”
Section: B !!! Vitro Studiesmentioning
confidence: 98%
“…It should also be noted that Roberts and Mitchell (1972) did not find evidence of greater metabolism of the labelled amino acids when the co~ds were preincubtted for 40 minut~s in the presence of either (1 C)-glycine, 1-(1 C)serine or L-(14C)glutamate. For instance, in view of their positive results after the stimulation of the rostral cord, one would have expected (14C)glycine to be released in their experim~nts in which incubations were carried out in the presence of L-(14C)serine, since the latter is readily converted to glycine (Shank and Aprison, 1970a;McBride et al, 1973). Mulder and Snyder (1974) have shown that a glycine-pool labelled by the high affinity uptake system, is more efficiently released from rat spinal cord slices, than cortex slices upon stimulation in vitro by ~.…”
Section: B Release O~ Glycinementioning
confidence: 98%
See 2 more Smart Citations
“…It has been generally accepted that the main reaction in the degradation of glycine is catalyzed by the glycine synthase (EC 2.1.2.10) [4] which splits it into C 0 2, N H 3 and methylene tetrahydrofolate (methylene-FH4). This reaction seems to be quantitatively coupled in the central nervous system (CNS) to the formation of serine [5], by the serine hydroxymethyltransferase catalyzed reaction, which can act in some circumstances as a degradative enzyme for glycine [6][7][8], both being enzymes located in the mitochondria [9][10][11][12].…”
mentioning
confidence: 99%